Evaluation of the HemoCue® for blood loss estimation in suction fluid in patients undergoing neurosurgical procedures: A prospective observational study - Y S Ranjitha; Anita N Shetty; Indrani Hemantkumar; Gauri R Gangakhedkar; Ashwini Choudhari (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Blood loss in neurosurgical procedures can be rapid and tremendous leading to consequential hemodynamic instability. HemoCue is a portable photometer used for the measurement of blood hemoglobin concentration. Using this point of care device, we contemplated this study to assess the reliability of HemoCue for suction hemoglobin determination and calculation of surgical blood loss by comparing with the gold standard laboratory Coulter Counter method in patients undergoing neurosurgical procedures. Material and Methods: This prospective observational study was conducted in 233 patients undergoing elective neurosurgical procedures in the age group of 18 to 60 years and having preoperative hemoglobin (Hb) values above 9 g/dL. Values of preoperative hemoglobin, suction hemoglobin, and volume in the suction container were used to obtain the estimated blood loss. The normality of the data was tested using the Kolmogorov Smirnov test. Bland Altman analysis was used to test the reliability of HemoCue in estimating hemoglobin and blood loss with reference to the gold standard laboratory Coulter Counter automated hematology analyzer. Results: Median blood loss calculated in our study using HemoCue was 554.65 mL with an interquartile range of 336.81 mL to 982.39 mL. Laboratory counter method estimated median blood loss was 533.37 mL with an interquartile range of 335.21 mL to 994.73 mL. The majority of the data obtained and analyzed using the Bland and Altman analysis method were within a 95% confidence interval. Conclusion: The HemoCue method is a reliable method and henceforth can be used to estimate blood loss in suction fluid in patients undergoing neurosurgical procedures.